COVID-19 Infection and its Relation to Preterm Delivery in Pregnant Women (Medico Legal Update, 2021)
The study aims to find the relationship between COVID-19 virus infections and early births in womeninfected with this virus in of Al-Fallujah city. The prospective study was conducted in Al-Fallujah cityduring the period between February 1, 2020, and September 1, 2020, at Al-Fallujah Teaching Hospital.Through the study, 100 pregnant women were received, complaining of Covid-19 infections, which werediagnosed in Al-Fallujah, and now Real Time PCR was confirmed through nasopharyngeal swabs that weretaken from Al-Fallujah Teaching Hospital. The study also included measuring the level of blood pressure,sugar andC-RP in those women during the fifth to eight week, where we were infected, and then in the 12thweek of pregnancy took place, where communication was made, and a level was measured, and as a result,these women whocompleted the period with a pre-term labor, miscarriagebefore the 24th week of pregnancyor those completed the period with successful pregnancy. In this study, 33% of COVID-19 pregnant womenwere within the age group 24-30 years followed by 30% in the age group 31-38 year. In this study, 10 % ofCOVID-19 pregnant women suffer from hypertension, 13% were with Diabetes, 35% with UTI while 70%were suffered from fever.When reaching 24th week of pregnancy, and as shown in Table 3. The study showedthat 40% COVID-19 pregnant women experienced completed the period with a pre-term labor, 10% waswith miscarriagebefore the 24thweek of pregnancy, while 50% of them completed the period continued thepregnancy. In this study, 82.5 % of COVID-19 pregnant women with preterm labor were suffered previouslyfrom fever comparing with 55% of COVID-19 pregnant women without preterm labor. The study showed thehighest mean of C-reactive protein was present COVID-19 pregnant women with preterm labor (22.5±2.14mg/ml), fan lowest mean was in women who without preterm labor (14.6±2.11 mg/ml) (P